(untitled) (Salud, Arte y Cuidado, 2020)
The objective of this research was to analyze the clinical and epidemiological characterizations in patients with a diagnosis of scabies in the Sanitary Dermatology consultation of the Adarigua Outpatient Clinic. Retrospective, non-experimental descriptive research, the medical records of 126 patients consulted in 2018 was reviewed, in a form type data collection sheet, applied with prior authorization by the director of the Adarigua outpatient clinic. The data collected were processed and the measures of relative frequency (percentage). The results regarding the sociodemographic characteristics reported in the records of adult patients predominate 65% female, while pediatric patients predominate 52% male, the consultation months with the highest number of adult patients were January, February, followed by June, October, May and November respectively, while pediatric patients were January and October. On the other hand, the findings of the clinical characterization report the histories of adult patients that 94% present intense itching, 91% eruptions with bumps and 91% do not present hyperkeratotic in the hands and feet; 97% do not present adenopathy and pediatric patients 57% present intense itching, 75% eruptions with bumps and 52% present hyperkeratotic in the hands and feet and 95% do not present adenopathy, on the other hand the type of lesions of adult patients are characterized by To be 85% extensive and 15% are localized and pediatric patients 29% extensive and 71%, the prescribed treatment of adult patients was 100% Ivermectina tablets, topical Permethrin, Dexpanthenol Cream, Antihistamine and recommendations for Hygiene Measures, while that prescribed in pediatric patients Permethrin 99%, Dexpanthenol cream 100%, Antihistamines 76% drops, 16% suspension and 11% tablets recommendations for hygienic measures in 100% of cases.